We have that
the expression 2f + 4f + 2 – 3-------> we can group it (2f+4f)+(2-3)
(2f+4f)+(2-3)=(6f-1)
therefore
the expression [2f + 4f + 2 – 3] is equivalent to [6f-1]
if the expression [6f-1] for f=3 is 17
then
the expression [2f + 4f + 2 – 3] for f=3 is also 17
<span>let's check it
</span>[2*3 + 4*3 + 2 – 3]--------> [6+12+2-3]=[20-3]=17------> is ok
Answer: 45
Step-by-step explanation:
Answer:
Step-by-step explanation:
convert mixed fractions to improper fractions
rule=a b/c=(ac+b)/c
(1 1/3)/(1 3/4)
(4/3)/(7/4)
rule for dividing fractions=(a/b)/(c/d)=(a/b)(d/c)
(4/3)(4/7) then you can multiply the numerators and denominators
16/21